Cold Pulsatile Machine Perfusion Versus Static Cold Storage for Kidneys Donated After Circulatory Death: A Multicenter Randomized Controlled Trial. Issue 5 (May 2020) - Summers, Dominic M.; Ahmad, Niaz; Randle, Lucy V.; O'Sullivan, Ann-Marie; Johnson, Rachel J.; Collett, David; Attia, Magdy; Clancy, Marc; Tavakoli, Afshin; Akyol, Murat; Jamieson, Neville V.; Bradley, J. Andrew; et al.
Abstract : Background: The benefits of cold pulsatile machine perfusion (MP) for the storage and transportation of kidneys donated after circulatory death are disputed. We conducted a UK-based multicenter, randomized controlled trial to compare outcomes of kidneys stored with MP versus static cold storage (CS). Methods: Fifty-one pairs of kidneys donated after circulatory death were randomly allocated to receive static CS or cold pulsatile MP. The primary endpoint, delayed graft function, was analyzed by "intention-to-treat" evaluation. Results: There was no difference in the incidence of delayed graft function between CS and MP (32/51 (62.8%) and 30/51 (58.8%) P = 0.69, respectively), although the trial stopped early due to difficulty with recruitment. There was no difference in the incidence of acute rejection, or in graft or patient survival between the CS and MP groups. Median estimated glomerular filtration rate at 3 months following transplantation was significantly lower in the CS group compared with MP (CS 34 mL/min IQR 26–44 vs MP 45 mL/min IQR 36–60, P = 0.006), although there was no significant difference in estimated glomerular filtration rate between CS and MP at 12 months posttransplant. Conclusions: This study is underpowered, which limits definitive conclusions about the use of MP, as an alternative to static CS. It did not demonstrate that the use of MP reduces the incidence of delayed graft function in donation after circulatory death kidney transplantation. Abstract : Supplemental Digital Content is available in the text.